2007
DOI: 10.1016/j.ejphar.2007.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate induces anti-migratory effects and inhibition of neutral phosphatases in UMR106 osteosarcoma cells

Abstract: Bisphosphonates are nonhydrolysable pyrophosphate analogues that prevent bone loss in several types of cancer. However, the mechanisms of anticancer action of bisphosphonates are not completely known. We have previously shown that nitrogen-containing bisphosphonates directly inhibit alkaline phosphatase of UMR106 rat osteosarcoma cells. In this study, we evaluated the effects of alendronate on the migration of UMR106 osteosarcoma using a model of multicellular cell spheroids, as well as the alendronate effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
3
8
0
3
Order By: Relevance
“…On the other hand, both advanced glycation endproducts and lower doses of Alendronate (10 − 6 M) could be inhibiting mainly divalent cation-independent neutral phosphatases (such as tyrosine phosphatases). Interestingly, we have previously shown that osteoblastic neutral phosphatase activity decreases by 45% in the presence of Vanadate (an inhibitor of tyrosine phosphatases) (Molinuevo et al, 2007), which is a degree of inhibition similar to that which we have found for advanced glycation endproducts and for 10 − 6 M Alendronate in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…On the other hand, both advanced glycation endproducts and lower doses of Alendronate (10 − 6 M) could be inhibiting mainly divalent cation-independent neutral phosphatases (such as tyrosine phosphatases). Interestingly, we have previously shown that osteoblastic neutral phosphatase activity decreases by 45% in the presence of Vanadate (an inhibitor of tyrosine phosphatases) (Molinuevo et al, 2007), which is a degree of inhibition similar to that which we have found for advanced glycation endproducts and for 10 − 6 M Alendronate in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Although we have not directly proven it, the same modulation of signal transduction mechanisms is probably operating under our experimental conditions. We have previously shown that different doses of bisphosphonates can inhibit both neutral and alkaline osteoblastic phosphatases (Vaisman et al, 2005;Molinuevo et al, 2007). In addition, other investigators have demonstrated that intracellular protein phosphorylation is essential for the process of osteoblastic differentiation (Xiao et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ho we ver, only a few stu di es ha ve in vol ved tu mo ri ge nic cell li nes (i.e., ne u roblas to ma and gli ob las to ma cell li nes). [15][16][17][18][19][20] In the few exis ting stu di es, sing le tu mo ri ge nic and/or non-tumo ri ge nic cells we re co-cul tu red with the se bi opoly mers over the long term to de ter mi ne whet her they we re ab le to form a sphe ro id or not. 19,20 These cells in fact for med sphe ro ids with the bi o polymers and sub se qu ently con ti nu ed the co-cul tu re pro cess over the long term.…”
mentioning
confidence: 99%